Inflammation: The Common Pathway of Stress-Related Diseases - Liu, Yun-Zi; Wang, Yun-Xia; Jiang, Chun-Lei (Frontiers in human neuroscience, 2017)
While modernization has dramatically increased lifespan, it has also witnessed that the nature of stress has changed dramatically. Chronic stress result failures of homeostasis thus lead to various diseases such as atherosclerosis, non-alcoholic fatty liver disease (NAFLD) and depression. However, while 75%-90% of human diseases is related to the activation of stress system, the common pathways between stress exposure and pathophysiological processes underlying disease is still debatable. Chronic inflammation is an essential component of chronic diseases. Additionally, accumulating evidence suggested that excessive inflammation plays critical roles in the pathophysiology of the stress-related diseases, yet the basis for this connection is not fully understood. Here we discuss the role of inflammation in stress-induced diseases and suggest a common pathway for stress-related diseases that is based on chronic mild inflammation. This framework highlights the fundamental impact of inflammation mechanisms and provides a new perspective on the prevention and treatment of stress-related diseases.